2023
DOI: 10.2478/azibna-2023-0003
|View full text |Cite
|
Sign up to set email alerts
|

Potential implications of natural antioxidants from plant to improve nutritional quality, oxidative stability and lipid degradation of egg yolk: A review

Florentina Tuță,
Mihaela Dumitru,
Tatiana Dumitra Panaite
et al.

Abstract: Food occupies a principal role in human life, having a major impact on health status and representing diverse characteristics that ensure valuable nutrient intake. Ensuring human nutrition has become one of the essential problems facing mankind, and quantity, quality and proper use of food have a major effect on the human body. Many raw materials and food products spoil easily, considerably shortening their shelf life. Extending the shelf-life of food is required to remove seasonal consumption, enlarge availab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 105 publications
(108 reference statements)
0
1
0
Order By: Relevance
“…The goose population increased from 1 million 374 thousand in 2020 to 1 million 478 thousand in 2021 according to data from TÜİK (2022). While extensive research has explored antioxidant concentrations in egg yolks, egg quality, antioxidant stability, and nutritional benefits for poultry progeny and human health worldwide (Rezaei et al, 2019;Kljak et al, 2021;Tuță et al, 2023), studies specifically focusing on geese remain limited (Chen et al, 2015;Ma et al, 2020;Fu et al, 2022). Notably, several studies have reported that antioxidant content in eggs positively influences hatching parameters and chick viability post-hatching.…”
Section: Introductionmentioning
confidence: 99%
“…The goose population increased from 1 million 374 thousand in 2020 to 1 million 478 thousand in 2021 according to data from TÜİK (2022). While extensive research has explored antioxidant concentrations in egg yolks, egg quality, antioxidant stability, and nutritional benefits for poultry progeny and human health worldwide (Rezaei et al, 2019;Kljak et al, 2021;Tuță et al, 2023), studies specifically focusing on geese remain limited (Chen et al, 2015;Ma et al, 2020;Fu et al, 2022). Notably, several studies have reported that antioxidant content in eggs positively influences hatching parameters and chick viability post-hatching.…”
Section: Introductionmentioning
confidence: 99%